The Philae Lander: Science planning and operations. (August 2016) - Moussi, Aurélie; Fronton, Jean-François; Gaudon, Philippe; Delmas, Cédric; Lafaille, Vivian; Jurado, Eric; Durand, Joelle; Hallouard, Dominique; Mangeret, Maryse; Charpentier, Antoine; Ulamec, Stephan; Fantinati, Cinzia; et al.
Abstract: Rosetta is an ambitious mission launched in March 2004 to study comet 67P/Churyumov–Gerasimenko. It is composed of a space probe (Rosetta) and the Philae Lander. The mission is a series of premieres: among others, first probe to escort a comet, first time a landing site is selected with short turnaround time, first time a lander has landed on a comet nucleus. In November 2014, once stabilized on the comet, Philae has performed its "First Science Sequence". Philae's aim was to perform detailed and innovative in-situ experiments on the comet's surface to characterize the nucleus by performing mechanical, chemical and physical investigations on the comet surface. The main contribution to the Rosetta lander by the French space agency (CNES) is the Science Operation and Navigation Center (SONC) located in Toulouse. Among its tasks is the scheduling of the scientific activities of the 10 lander experiments and then to provide it to the Lander Control Center (LCC) located in DLR Cologne. The teams in charge of the Philae activity scheduling had to cope with considerable constraints in term of energy, data management, asynchronous processes and co-activities or exclusions between instruments. Moreover the comet itself, its environment and the landing conditions remained unknown until separation time. The landing site was selected once the operational sequence was already designed. This paper will explain the specific context of the Rosetta lander mission and all the constraints that the lander activity scheduling had to face to fulfill the scientific objectives specified for Philae. A specific tool was developed by CNES and used to design the complete sequence of activities on the comet with respect to all constraints. The baseline scenario for the lander operation will also be detailed as well as the sequence performed on the comet to highlight the difficulties and challenges that the operational team faced. Highlights: Introduction to Rosetta and Philae mission including ops organization. Constraints to be considered for the science planning. Baseline sequence prepared. Update of the sequence during landing site selection. Science sequence performed during operations.